Pilot deep RNA sequencing of worker blood samples from Singapore printing industry for occupational risk assessment - Guo, Nancy Lan (2022)
Several engineered nanomaterials (ENMs) are used in toner-based printing equipment (TPE) including laser printers and photocopiers to improve toner performance. High concentration of airborne nanoparticles due to TPE emissions has been documented in copy centers and chamber studies. Recent animal inhalation studies by our group suggested exposure to laser printer-emitted nanoparticles (PEPs) increased cardiovascular risk by impairing ventricular performance and inducing hypertension and arrhythmia, consistent with global transcriptomic and metabolomic profiling results. There has been no genome-wide transcriptomic analysis of workers exposed to TPE emissions to systematically assess the occupational exposure health risks. In this pilot study, deep RNA sequencing of blood samples of workers in two printing companies in Singapore was performed. The genome-scale analysis of the blood samples from TPE exposed workers revealed perturbed transcriptional activities related to inflammatory and immune responses, metabolism, cardiovascular impairment, neurological diseases, oxidative stress, physical morphogenesis/deformation, and cancer, when compared with the control peers (office workers). Many of these disease risks associated with particle inhalation exposures in such work environments were consistent with the observation from the PEPs rat inhalation studies. In particular, the cell adhesion molecules (CAMs) was a top significantly perturbed pathway in blood samples from exposed workers compared with the office workers in both companies. The protein expression of sICAM was verified in plasma of exposed workers, showing a positive correlation with daily average nanoparticle concentration in indoor air measured in these two companies. Larger scale genomic and molecular epidemiology studies in copier operators are warranted in order to assess potential risks from such particulate matter exposures.